Optical tomography: A review on sensor array, projection arrangement and image reconstruction algorithm - Siti Zarina, Mohd. Muji; Ruzairi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman; Shafishuhaza, Sahlan; Mohd Fadzli, Abdul Shaib; Muhammad, Jaysuman; Elmy Johana, Mohamad (Kyushu Tokai University, 2011)
Link to publisher's homepage at http://www.ktokai-u.ac.jp/